2012
DOI: 10.1002/j.0022-0337.2012.76.10.tb05386.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Patient Grievances in a Dental School Clinical Environment

Abstract: Patient satisfaction is an integral part of assessing the quality of oral health care. As dental care becomes more impersonal, competitive, and expensive, the potential for patient complaints is on the rise. Dental school clinics may be more vulnerable to patient grievances due to inexperienced student providers, less eficient delivery of care, challenges related to continuity of care, and the complexity of adhering to institutional policies. Effective management of patient complaints can assist both individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In that study, some students felt that procedures were done for the sake of requirements, without looking at the patient holistically. A potential strategy to better engage patients in treatment is to assign them to student teams rather than an individual student 29 . Such a system allows fourth‐year students to complete more difficult procedures and ensures that third‐year students are involved in treating the patient and patients do not have to repeat their personal history again from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, some students felt that procedures were done for the sake of requirements, without looking at the patient holistically. A potential strategy to better engage patients in treatment is to assign them to student teams rather than an individual student 29 . Such a system allows fourth‐year students to complete more difficult procedures and ensures that third‐year students are involved in treating the patient and patients do not have to repeat their personal history again from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to communicate with patients, listen, be observant and respond to patients' needs, empathise, understand and carry out consultations in an organised and professional manner are considered as basic requirements of a competent dentist . Patient complaints regarding dental appointments have commonly included communication problems with their dentist . Effective communication could further aid and hasten the diagnostic process and decision‐making and enhance patient–clinician understanding .…”
Section: What Are Soft Skills?mentioning
confidence: 99%
“…The third most reported (34.9%) reason reported by the DS group in our study for not providing adequate periodontal care was an institutional factor: that multiple providers are involved in patient care. Sachdeo et al found that a majority of patient grievances in a dental school clinic were related to continuity of care issues resulting from students’ graduation and the transfers thereafter 11 . They proposed a Vertical Integration Protocol as a remedy for this problem, by which a patient is coassigned to students in different years of training from the first to fourth years.…”
Section: Discussionmentioning
confidence: 99%